Latin American conciliar ecclesiology and historiographic discourse: a critical study of The Church in Peru by Jeffrey Klaiber S. J. - Espinoza Portocarrero, Juan Miguel (2020)
The book La Iglesia en el Perú written by Jeffrey Klaiber S.J. is a classic of necessary consultation for the study of Catholicism in the 19th and 20th centuries in Peru. As a tribute to Jeffrey Klaiber, the authors analyze the ecclesiological bases of the historical narrative of La Iglesia en el Perú. The article highlights how Klaiber’s work is shaped by the process of reception of the Second Vatican Council (1962-1965) mediated by the General Conferences of the Latin American Episcopate gathered in Medellín (1968) and Puebla (1979). Besides, it examines the temporal division of La Iglesia en el Perú, which distinguishes between the 19th century, the first half of the 20th century, and the conciliar reception from 1955 to 1985. The text draws on Klaiber’s contributions, limitations, and the perspectives it opened for subsequent scholar research on Peruvian Catholicism.